Penegakan Hukum Bagi Pengguna Aplikasi Michat Sebagai Sarana Tindak Pidana Prostitusi Online Dikaitkan Dengan UU Republik Indonesia Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik - Yuni Shaputri, Siti Nurewah; Mulyana, Yusep (Universitas Ekasakti, 2024)
The city of Bandung is one of the regions in Indonesia where the practice of online prostitution or the crime of human trafficking is rampant. Business people take advantage of accommodation facilities in the city of Bandung. The perpetrators took advantage of the ease of access to communicate by using the Michat application with fellow users who were located relatively close by. This business uses it as a service offering sexual services to potential consumers or users of the same application. The analytical tool used is legal interpretation, namely legal interpretation. Legal interpretation or legal interpretation itself is an effort to explain, explain, confirm both in a broad and narrow sense the existing legal understanding to use it to solve the problem being faced. The results of the research show that the regulation regarding the Michat application as a criminal act of online prostitution is determined in Article 27 paragraph (1) of Law Number 1 of 2024 because the seller or alter deliberately uses the MiChat application to promote sexual services by broadcasting electronic information which clearly has content that violates decency. Proof for perpetrators of criminal acts on the Michat application is that chat history, profile photos and other information obtained from the MiChat application can be used as valid legal evidence as stipulated in Article 5 of Law Number 1 of 2024. And the efforts made by the government for users The Michat application is a preventive effort carried out to prevent the practice of online prostitution, and a repressive effort carried out by closing localization places in various regions, imprisoning (ultimatum remndium) for commercial sex workers for violating Article 27 paragraph (1) of the Law Number 1 of 2024.